دور المرصد الوطني للمجتمع المدني في تعزيز قيم المواطنة - مازوزي، جمال; الخذير، علي (جامعة الوادي University of El Oued, 2024)
تعد قضية تعزيز المواطنة والمحافظة عليها وحمايتها من القضايا التي تفرض نفسها على المجتمع ويعود ذلك إلى ظهور مشكلات متعلقة بالعولمة، والعالمية مختلفة تهدد اللحمة الوطنية والهوية الثقافية، مما يفرض على الحكومات ومؤسسات المجتمع المدني ضرورة تكاتف وتكاثف الجهود العاجلة لتصدي لها في ظل الغزو الحضري الغربي السريع. وفي هذا الإطار يجب تزايد دور الجمعيات والهيات وغيرها من المنظمات ومؤسسات المجتمع المدني التي أصبحت تساهم بدور أساسي في توسيع النقاش والحوار والاقتراح والاستعداد للأخطار التي تهدد قيم المواطنة ونشر الوعي المجتمعي، وتقوم الجزائر بمجهودات كبيرة في هذا المجال إلا أنها غير كافية في ظل زيادة المشكلات المواطنة وتفشي السلوكيات المضرة بتعزيز قيم المواطنة من طرف المواطنين، ومن هذا المنطلق تهدف هذه الدراسة الوصفية التحليلية إلى مناقشة دور المرصد الوطني للمجتمع المدني من خلال تعزيز قيم المواطنة في الجزائر. The issue of promoting، preserving and protecting citizenship is one of the issues that imposes itself on Society. This is due to the emergence of various problems related to globalization and internationalism that threaten national cohesion and cultural identity، which imposes on governments and civil society institutions the need to join forces and intensify urgent efforts to confront them in light of the rapid Western urban invasion. In this context، the role of associations، bodies، and other organizations and civil society institutions must increase، which have become a fundamental contributor to expanding discussion، dialogue، and proposals، and preparing for dangers that threaten the values of citizenship and spreading societal awareness. Algeria is making great efforts in this field، but they are insufficient in In light of the increase in citizenship problems and the spread of behaviors that are harmful to the promotion of citizenship values by citizens، and from this standpoint، this descriptive and analytical study aims to discuss the role of the National Observatory for Civil Society by promoting citizenship values in Algeria
ماستر سياسة عامة